2005
DOI: 10.1002/jcb.20466
|View full text |Cite
|
Sign up to set email alerts
|

Wnt‐mediated regulation of chondrocyte maturation: Modulation by TGF‐β

Abstract: Wnt proteins are expressed during limb morphogenesis, yet their role and mechanism of action remains unclear during long bone growth. Wnt expression, effects and modulation of signaling events by BMP and transforming growth factor-beta (TGF-β) were evaluated in chick embryonic chondrocytes. Chondrocyte cell cultures underwent spontaneous maturation with increased expression of colX and this was associated with an increase in the expression of multiple Wnts, including Wnts 4, 5a, 8c, and 9a. Both parathyroid ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 49 publications
4
58
1
3
Order By: Relevance
“…thermore, we demonstrated that TGF-␤ treatment inhibits activation of the TOPflash promoter by ␤-catenin in chick upper sternal chondrocytes (6). Although these findings seemingly contradict the current observation that TGF-␤ induces ␤-catenin signaling through a SMAD3-mediated mechanism, important differences between the culture models likely account for the discrepancy in the findings.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…thermore, we demonstrated that TGF-␤ treatment inhibits activation of the TOPflash promoter by ␤-catenin in chick upper sternal chondrocytes (6). Although these findings seemingly contradict the current observation that TGF-␤ induces ␤-catenin signaling through a SMAD3-mediated mechanism, important differences between the culture models likely account for the discrepancy in the findings.…”
Section: Discussioncontrasting
confidence: 76%
“…We (6) and others (34) have shown that ␤-catenin induces prehypertrophic chondrocytes to complete terminal maturation. Overexpression of ␤-catenin or addition of Wnt3a, which induces the canonical ␤-catenin signaling pathway, stimulates expression of colX and other maturational markers (6,34).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations